SPP1+ macrophages in tumor immunosuppression: mechanisms and therapeutic implications - Wang, Juanjuan; Wang, Ya; Liu, Yuqing; Yang, Rongcun (Frontiers in Immunology, 2025)
Secreted phosphoprotein 1 (SPP1+) macrophages are a recurrent and functionally critical immune cell subset across multiple cancer types. They drive adverse clinical outcomes by promoting immunosuppression, tumor invasion, metastasis, and therapy resistance. Given their prevalence and pivotal role, SPP1+ macrophages have become a major focus in cancer immunology and a promising target for therapeutic development. SPP1+ macrophages have been identified in a wide range of human malignancies through single-cell RNA sequencing and spatial transcriptomics studies. Their differentiation and maintenance are strongly influenced by reciprocal cellular interactions and hypoxic conditions within the tumor microenvironment (TME). Within the tumor microenvironment (TME), SPP1+ macrophages promote tumor progression by interacting with cancer-associated fibroblasts (CAFs) and helping to form a physical barrier that restricts immune cell infiltration into the tumor core. Specifically, they impair the recruitment of CD8+ T cells and promote T cell exhaustion (TEX). In this review, we focus on recent advances in understanding the differentiation of SPP1 macrophages in hypoxic tumor microenvironment and the role of SPP1+ macrophages in immunosuppression and their therapeutic implications in cancer. Targeting this subset of macrophages has emerged as a highly promising therapeutic strategy, with several approaches demonstrating encouraging results in preclinical models.